Experimental Analysis of Heat Storage and Release of Binary Methanol Aqueous Solution Pulsating Heat Pipe Phase Change Accumulator - Lu, Xiaohui; Luo, Xiaoxue; Cao, Shibo; Zou, Changzhen (Frontiers in Energy Research, 2022)
In order to improve the problems of energy shortage and low utilization rate, this paper couples the pulsating heat pipe with the phase change energy storage material, designs a set of pulsating heat pipe heat storage and release device, and builds an experimental platform, using the latent heat storage technology of the phase change material, further optimize the heat transfer performance of the device. The experimental filling working fluid is a binary methanol-water solution with a filling rate of 0.6 (methanol and water are 0.3 respectively). Experiments were carried out to study the heat storage and heat release performance under different flow rates and different heating temperatures. The results show that when the binary methanol-water solution is used as the filling working fluid, when the heat source inlet flow rate is 0.60m3/h and the heat source heating temperature is 120℃, the heat storage performance is better; when the heat is released, the lower the initial temperature of cooling water, the higher the heat recovery rate. The experiment in this paper can provide a certain reference value for actual production.